Tinjauan Literatur Sistematis Terhadap Penerapan Sistem Klasifikasi Khusus Di Perpustakaan - Nurhayati, Euis Sri; Mayesti, Nina (UI Scholars Hub, 2023)
The Dewey Decimal Classification (DDC) is a widely implemented classification system in most libraries. However, its usage has declined over the past four decades, and libraries are advised to undergo reclassification. Conversely, it is recognized that the implementation of specialized classification systems significantly impacts information retrieval. Therefore, the aim of this study is to elucidate the concept and methodology behind the integration of bespoke categorization frameworks within diverse libraries across Indonesia over the past decade. This study employs the Systematic Literature Review (SLR) and the Population, Intervention, Comparison, Outcome, and Context (PICOC) framework to analyze ideas, schemes, processes, and challenges in implementing specialized classification systems. Scientific articles sourced from Google Scholar were utilized for the review. Ten scientific articles were selected for analysis after successfully passing the literature quality assessment stage. The data were examined and analyzed by describing the research content, addressing issues in its formulation, and drawing conclusions from the scientific articles. According to the study's findings, the development of a specialized classification system is contingent upon the interpretation of ideas, the nature of collections, and the complexity of their contents. The primary distinction between utilizing a specialized classification system and a general classification system lies in the ease of the process. The application of a specialized classification system in various Indonesian libraries is based on ideological, practical, and empirical considerations.